2021
DOI: 10.3390/antibiotics10080914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Delivery Methods in Phage Therapy against Flavobacterium columnare Infections in Rainbow Trout

Abstract: Viruses of bacteria, bacteriophages, specifically infect their bacterial hosts with minimal effects on the surrounding microbiota. They have the potential to be used in the prevention and treatment of bacterial infections, including in the field of food production. In aquaculture settings, disease-causing bacteria are often transmitted through the water body, providing several applications for phage-based targeting of pathogens, in the rearing environment, and in the fish. We tested delivery of phages by diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The high mortality in untreated germ-free fish, and the fact that we saw no mortality in phage-treated germ-free fish, showed that bacteriophage therapy was successful in increasing survival during infection with F. columnare . The same phage that we used (FCL-2) has also been successfully used earlier in rainbow trout and zebrafish, where elevated survival was observed 38 , 40 . Our findings therefore confirm the potential of using this phage in aquaculture against F. columnare infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high mortality in untreated germ-free fish, and the fact that we saw no mortality in phage-treated germ-free fish, showed that bacteriophage therapy was successful in increasing survival during infection with F. columnare . The same phage that we used (FCL-2) has also been successfully used earlier in rainbow trout and zebrafish, where elevated survival was observed 38 , 40 . Our findings therefore confirm the potential of using this phage in aquaculture against F. columnare infections.…”
Section: Discussionmentioning
confidence: 99%
“…This disease is caused by the bacterium Flavobacterium columnare , which infects, amongst others, salmonid fish 4 , 36 , 37 . While antibiotics is the common line of treatment, bacteriophage therapy against F. columnare in aquaculture systems has been demonstrated with promising results 38 40 .…”
Section: Introductionmentioning
confidence: 99%
“…Phage therapy in aquaculture became a greener and safer alternative to the use of antibiotics [ 167 ]. Phage-based pathogen targeting has a variety of uses in both fish and the environment where they are raised [ 168 ].…”
Section: Phage Delivery Strategies For Animal Health and Food Applica...mentioning
confidence: 99%
“…Kunttu et al [ 168 ] evaluated the use of phages to prevent and treat infections by Flavobacterium columnare in rainbow trout by using several phage delivery techniques such as via baths, via phage-coated materials, and via oral delivery in fish feed. In this case, the most effective phage therapy procedure consisted in applying phages via bath exposure immediately after the first symptoms of the disease appeared in the fish population.…”
Section: Phage Delivery Strategies For Animal Health and Food Applica...mentioning
confidence: 99%
“…This disease is caused by the bacterium Flavobacterium columnare, which infects, amongst others, salmonid fish [4,36,37] . While antibiotics is the common line of treatment, bacteriophage therapy against F. columnare in aquaculture systems has been demonstrated with promising results [38][39][40] .…”
Section: Introductionmentioning
confidence: 99%